Tuesdays with Morrie : an old man, a young man and life's greatest lesson - Albom, Mitch (New York : Anchor Books, 1997)
Tuesdays with Morrie is a moving memoir that recounts the real-life conversations between the author, Mitch Albom, and his former college professor, Morrie Schwartz, who is dying from ALS (Lou Gehrig$1 (Bs disease). After years without contact, Mitch reconnects with Morrie after seeing him in a television interview. He then begins visiting Morrie every Tuesday, turning their final months together into powerful lessons on life.s
Keywords: Schwartz, Morrie -- Health; Schwartz, Morrie -- Interviews; Amyotrophic lateral sclerosis -- Patients -- United States -- Biography; College teachers -- United States -- Biography